Comparison of bone tissue trace-element concentrations and mineral density in osteoporotic femoral neck fractures and osteoarthritis - Karaaslan, Fatih (Dove Medical Press, 2014)
PURPOSE: This study examined the role of trace elements in osteoporosis by comparing the trace-element concentrations in bone and the radiographic bone density and bone mineral density (BMD) of patients with osteoporotic femur fractures and osteoarthritis. PATIENTS AND METHODS: The study enrolled 30 patients operated on for proximal femoral fractures after falls, and another 30 patients undergoing hip arthroplasty at the same center for hip osteoarthritis. Bone samples were obtained during the surgical procedures. The density of the bone samples was assessed using computed tomography and the Hounsfield scale. The levels of Ca(II), Mg(II), and other trace elements in the bone samples were determined using flame atomic absorption spectrometry and inductively coupled plasma mass spectrometry. In addition, BMD, Z-scores, and T-scores were measured in the unaffected hips of all patients using dual-energy X-ray absorptiometry. RESULTS: Magnesium (1,908±507 versus 2,540±435, P<0.05), calcium (10.4±3.5 versus 13.9±3.7, P<0.05), and zinc (2,342±1,252 versus 3,145±1,604, P<0.05) μg g(−1), levels were significantly lower in the bone samples in the fracture group. The groups did not differ in the other biochemical parameters. All dual-energy X-ray absorptiometry findings were significantly worse in the fracture group than in the osteoarthritis group. However, the groups did not differ in femoral neck density assessed radiologically using the Hounsfield scale. The following parameters were negatively correlated with age: magnesium, r=−0.436, P<0.001; calcium, r=−0.331, P=0.01; T-score, r=−0.381, P=0.003; Z-score, r=−0.267, P=0.043; and BMD, r=−0.365, P=0.004. CONCLUSION: Ca(II), Mg(II), and Zn(II) appear to play important roles in bone breakdown/synthesis. Further studies of the roles of trace elements in the etiology and treatment of osteoporosis are warranted. We found decreased bone levels of Ca, Mg, and Zn in patients with osteoporotic fractures compared to subjects with osteoarthritis.